1992
DOI: 10.1055/s-2008-1063425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Hirschsprung-Associated Neuronal Intestinal Dysplasia (HANID)

Abstract: The rate of Hirschsprung-associated neuronal intestinal dysplasia (HANID) is reported to be as high as 20-75% but no report deals with its sequelae. The aim of our study was to evaluate the influence of the retained neuronal dysplastic segment in patients with Hirschsprung's disease (HD). We report on 47 patients with HD including 11 cases with HANID (23%). All 47 children had a Duhamel procedure subsequent to colostomy and in none of the 11 cases with HANID was the neuronal dysplastic segment resected. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 0 publications
1
23
1
2
Order By: Relevance
“…These observations support the hypothesis that IND B, hypoganglionosis of the myenteric plexus and aganglionosis, which are often combined, are developmental abnormalities with an identical pathogenesis [7,13,45]. This, however, contradicts the idea of Hanimann et al that the combination of aganglionosis and IND B (which they called "HANID") is a separate disease-entity [17], different from isolated Hirschsprung's disease and isolated IND B.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…These observations support the hypothesis that IND B, hypoganglionosis of the myenteric plexus and aganglionosis, which are often combined, are developmental abnormalities with an identical pathogenesis [7,13,45]. This, however, contradicts the idea of Hanimann et al that the combination of aganglionosis and IND B (which they called "HANID") is a separate disease-entity [17], different from isolated Hirschsprung's disease and isolated IND B.…”
Section: Discussioncontrasting
confidence: 55%
“…IND B combined with aganglionosis [5,10,15,17,19,25,34] is not morphologically different from isolated IND B. In 64 patients with Hirschsprung's disease and IND B, the biopsy diagnosis was generally made at 12_+6 months in comparison to 4+2 months in isolated Hirschsprung patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fadda et al [1] reported motility disorders in one-third of children with HaIND and Kobayashi et al [8] found defecation disorders in all of their patients with HaIND. Hanimann et al [3] described constipation in the early postoperative course in 18.2% of their patients with HaIND and 8.3% with isolated HD. All of their patients underwent a Duhamel procedure, without total resection of the IND segment if one was found.…”
Section: Discussionmentioning
confidence: 97%
“…1 IND can occur as an isolated form or in association with HD proximal to the aganglionic segment. A close association between IND and HD is recognized and was termed Hirschsprung-associated IND by Hanimann et al 2 The reported incidence of isolated IND varies from 0.3% to 62% of all rectal suction biopsies. 3 On the contrary, 25% to 35% of patients with HD have associated IND, frequently related to postoperative complications after definitive surgery for HD.…”
mentioning
confidence: 97%